The Influence of Lifestyle and Self-Control on the Consumptive Behavior of Generation Z in North Surabaya with Financial Literacy as a Moderating Variable - Vika Anikawati; Rahman Amrullah Suwaidi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Consumptive behavior is defined as purchasing actions that are driven more by desires than needs, often carried out with little deliberation. Utilizing financial literacy as a moderating variable, this study aims to examine how lifestyle and self-control influence the consumption patterns of Generation Z in North Surabaya. Primary data were collected through a quantitative approach using Google Forms to distribute the questionnaire. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0 software. The findings indicate that both self-control and lifestyle have a positive and significant effect on consumptive behavior. However, financial literacy does not moderate the relationship between lifestyle and consumptive behavior, although it does strengthen the relationship between self-control and consumptive behavior.